Handbook of physical vapor deposition (PVD) processing : - Mattox, D. M. (Noyes Publications, 1998)
This book covers all aspects of physical vapor deposition (PVD) process technology from the characterizing and preparing the substrate material, through deposition processing and film characterization, to post-deposition processing. The emphasis of the book is on the aspects of the process flow that are critical to economical deposition of films that can meet the required performance specifications.